AUTOMATED NUTRIENT CONTROL AND MONITORING SYSTEM FOR INTERNET OF THINGS (IOT)-BASED HYDROPONIC TOWERS - Muhammad, Waliyyuddin; Faridah, Linda; Sutisna (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
This research aims to design and implement an Internet of Things (IoT)-based nutrient control and monitoring system in the Hydroponic Tower system, as a solution to land limitations and manual monitoring challenges. The system utilizes a DS18B20 Temperature Sensor and a TDS Meter V1.0 KS0429 sensor for precision data acquisition, as well as an actuator in the form of a Yamano WP-103 pump and a DC 2W-160-15 Solenoid Valve controlled by an ESP32-DevKitC-1 Microcontroller. Data from the sensors is sent in real-time to the dashboard via the MQTT protocol, enabling automatic monitoring and control. This system successfully keeps environmental parameters such as pH, Temperature, and ppm in a stable range that is positively correlated with plant growth. This success was validated with a total harvest of 10,569kg and an average of 58.3grams per plant. In conclusion, the system is able to optimize the efficiency of tower hydroponic cultivation, offering an adaptive solution for precision farming in dense urban environments.